SIKAP MAHASISWA TERHADAP BAHASA INDONESIA DAN HUBUNGANNYA DENGAN PENCAPAIAN KOMPETENSI DASAR BAHASA INDONESIA - Zuhriyah, Ainu (BASTRA : Jurnal Penelitian Pendidikan Bahasa dan Sastra, 2015)
The general purpose of this research is to describe students’ attitude toward Bahasa Indonesia and its relation with their Bahasa Indonesia basic competence achievement at Rajekwesi Health Academy of Bojonegoro. Specifically, this research aims at (1) describing students’ language attitude toward Bahasa Indonesia, (2) describing students’ Bahasa Indonesia basic competence achievement, and (3) determining whether there is or there is not any relation between students’ language attitude and their Bahasa Indonesia basic competence achievement. This research was designed by using quantitative approach (descriptive and correlative). The data of this research were students’ language attitude and students’ Bahasa Indonesia basic competence achievement. The source of data for this research was the students of Rajekwesi Health Academy of Bojonegoro. The data were collected by means of documentation and questionnaire. The result of the study shows that students’ attitude toward Bahasa Indonesia was categorized enough. In general, there is no relation between students’ language attitude and their Bahasa Indonesia basic competence achievement.